Animal Models in Osteosarcoma - Guijarro, Maria V.; Ghivizzani, Steven C.; Gibbs, C. Parker (Frontiers in Oncology, 2014)
Osteosarcoma (OS) is the most common non-hematologic primary tumor of bone in children and adults. High-dose cytotoxic chemotherapy and surgical resection have improved prognosis, with long-term survival for non-metastatic disease approaching 70%. However, most OS tumors are high grade and tend to rapidly develop pulmonary metastases. Despite clinical advances, patients with metastatic disease or relapse have a poor prognosis. Towards a better understanding of the molecular pathogenesis of human OS several genetically modified OS mouse models have been developed and will be reviewed here. However better animal models that more accurately recapitulate the natural progression of the disease are needed for the development of improved prognostic and diagnostic markers as well as targeted therapies for both primary and metastatic OS.